Baladna Goes Global. (November 2021) - Allagui, Ilhem
Baladna is a dairy company in Qatar. It has thrived despite an ongoing political and economic blockade, helping the country to become self-sufficient in terms of its dairy needs. In a short time and with substantial investment, the brand became a market leader. Baladna's growth plan banks on globalization, but the marketing director and the VP of marketing disagree on the strategy: one argues for standardization and the other for adaptation. The case study discusses brand name issues as well as brand identity approaches in the context of a multicultural environment.